Análisis de contenidos de la programación infantil de: radio Latacunga AM, radio Hechizo y radio Municipal - Garcés Vega, Nathalie Guadalupe (2020)
This research was carried out to make a study about Latacunga’s children taking part in radio media. Its main goal is to make an analysis on the message contents that this childhood population in being exposed to, and their active participation. To accomplish this inquiry three different kind of radios were considered, a public, a private, and a community one. The study used a qualitative methodology, trough a program observation sheet to analyze the content of the programs set up by the above mentioned radios. An experimental group of children participated; they were asked about whether they have been taken into account to design the radio programs and how they hope those programs be like. The main findings were that there was a lack of a specific radio programing in the stations treated. However, there was a radio program in the community, but its content was poor, it was run by an adult and there was not childlike participation. As part of the investigation, a pilot program was implemented with children participation and the guidance of a communicator. The result was that the children felt legitimize, able to give their opinion and they also had meaningful learning experience. Hence, promoting this kind of infantile concurrence in radios brings out in an effective media tool and a way to apply Edu- communication. Then as a means of practicing the right to free expression, these high-quality programs should be developed